A Multi-Omics Analysis Suggests Links Between the Differentiated Surface Metabolome and Epiphytic Microbiota Along the Thallus of a Mediterranean Seaweed Holobiont - Paix, Benoît; Carriot, Nathan; Barry-Martinet, Raphaëlle; Greff, Stéphane; Misson, Benjamin; Briand, Jean-François; Culioli, Gérald (Frontiers in Microbiology, 2020)
Marine macroalgae constitute an important living resource in marine ecosystems and complex ecological interactions occur at their surfaces with microbial communities. In this context, the present study aimed to investigate how the surface metabolome of the algal holobiont Taonia atomaria could drive epiphytic microbiota variations at the thallus scale. First, a clear discrimination was observed between algal surface, planktonic and rocky prokaryotic communities. These data strengthened the hypothesis of an active role of the algal host in the selection of epiphytic communities. Moreover, significant higher epibacterial density and α-diversity were found at the basal algal parts compared to the apical ones, suggesting a maturation gradient of the community along the thallus. In parallel, a multiplatform mass spectrometry-based metabolomics study, using molecular networking to annotate relevant metabolites, highlighted a clear chemical differentiation at the algal surface along the thallus with similar clustering as for microbial communities. In that respect, higher amounts of sesquiterpenes, phosphatidylcholines (PCs), and diacylglycerylhydroxymethyl-N,N,N-trimethyl--alanines (DGTAs) were observed at the apical regions while dimethylsulfoniopropionate (DMSP) and carotenoids were predominantly found at the basal parts of the thalli. A weighted UniFrac distance-based redundancy analysis linking the metabolomics and metabarcoding datasets indicated that these surface compounds, presumably of algal origin, may drive the zonal variability of the epibacterial communities. As only few studies were focused on microbiota and metabolome variation along a single algal thallus, these results improved our understanding about seaweed holobionts. Through this multi-omics approach at the thallus scale, we suggested a plausible scenario where the chemical production at the surface of T. atomaria, mainly induced by the algal physiology, could explain the specificity and the variations of the surface microbiota along the thallus.